Indiana Steinhardt and the Quest for Quasicrystals : A Conversation with Paul Steinhardt. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Paul Steinhardt, the Albert Einstein Professor of Science and Director of the Center for Theoretical Science at Princeton University. This wide-ranging conversation provides a comprehensive account of a marvellous scientific adventure story in the quest for a natural quasicrystal. You will be taken on a fascinating ride through the physics of materials, from theory, to the laboratory, to the discovery of a new state of matter, that culminated in Paul Steinhardt's dramatic Siberian expedition. Paul Steinhardt talks.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Introducing Quasicrystals -- II. Building Models -- III. Out of the Blue -- IV. Competing Explanations -- V. Looking to Nature -- VI. New Year's Delight -- VII. Confronting the Impossible -- VIII. Tracking Khatyrkite -- IX. Kamchatka -- X. Passing It On -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Steinhardt, Paul J. -- Interviews; Quasicrystals; Quasicristaux; MATHEMATICS; Chemistry; SCIENCE; Geophysics; Physics; Condensed Matter; Quasicrystals; Interviews